Selective Social Belief Revision in Young Children. Issue 4 (7th August 2020) - Miosga, Nadja; Schultze, Thomas; Schulz-Hardt, Stefan; Rakoczy, Hannes
ABSTRACT: Recent research has shown that from early in development, children selectively form new beliefs in response to information supplied by others. However, little is known about the development of selective revision of existing beliefs in response to socially conveyed information. Such selective social belief revision has been extensively studied by social psychologists in the context of advice-taking. Here, we adapted the methods of this research tradition for studying selective advice-taking in young children and adults. Participants solved a perceptual judgment task, received advice, and subsequently made final decisions. The informational access (perceptual quality) of participants and advisor were experimentally manipulated. Adults revised their judgments systematically as a function of both their own and the advisor's informational access whereas children based their adjustments only on their own informational access. Two follow-up experiments suggest, however, that this pattern of results in children reflected performance rather than competence limitations: In suitably modified tasks, children did proficiently consider both their own informational situation and that of the advisor in their selective social belief revision.